2000
DOI: 10.1034/j.1399-0039.2000.560207.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of host‐ and virus‐related factors associated with spontaneous hepatitis C virus clearance

Abstract: Epidemiologic parameters, virologic characteristics and frequency of HLA class II DR and DQ antigens were compared between 63 subjects with spontaneous hepatitis C virus clearance (group 1) and 282 patients with chronic active hepatitis C virus infection (group 2). DRB1*1101 and moreover DQB1*0301 alleles were more frequent in group 1 than in group 2 (33.8% vs. 14.7% and 64.4% vs. 28.6%; P=0.012 and P=0.003, respectively). The frequency of DQB1*02 was lower in group 1 than in group 2 (25.4% vs. 49%; P=0.04). N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
54
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 17 publications
10
54
1
1
Order By: Relevance
“…In 2009, Ali et al, [32] studied the HCV prevalence in various age groups in which prevalence rate was more in males as compared to females in accordance with our study which was 12% in males young adults and 6% in females (Table3). The young female adults are little affected as compared to male young adults.…”
Section: Discussionsupporting
confidence: 88%
“…In 2009, Ali et al, [32] studied the HCV prevalence in various age groups in which prevalence rate was more in males as compared to females in accordance with our study which was 12% in males young adults and 6% in females (Table3). The young female adults are little affected as compared to male young adults.…”
Section: Discussionsupporting
confidence: 88%
“…4,16,17,25,32,35,39,41,52 One study, however, reported an opposite effect for DQB1*0301. 48 Several of these studies on susceptibility to HCV compared individuals with chronic HCV infection to healthy controls.…”
Section: Susceptibility To Persistent Hcv Infectionmentioning
confidence: 98%
“…54 Another allele that has been correlated with selflimiting HCV is DRB1*1101. 16,17,35,39,50 An Italian study found a protective role for the DR5 sero-group against HCV infection. 51 The molecularly-defined DRB1*1100 and DRB1*1200 groups of alleles are part of the serologically defined DR5 group.…”
Section: Susceptibility To Persistent Hcv Infectionmentioning
confidence: 99%
“…Such a significant difference is observed in a study conducted in the years 1999-2002 (21) (Figure 2). The least incidence of HCV in females could be attributed to low exposure to HCV risk factors due to male dominating society of the area and also the estrogens hormone in females is considered to play a role in the spontaneous clearance of HCV infection (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%